Working Memory and Deafness: Implications for Cognitive Development and Functioning - Keehner, Madeleine; Atkinson, J. (Academic Press, 2006)
Traditional conceptualizations of working memory (WM) make a number of well-founded assumptions about cognitive phenomena. Visuo-spatial and verbal processes are viewed as separable, and a sound-based phonological code is believed to underlie the processing of language. For deaf individuals, however, the typical assumptions may not apply. Linguistic inputs for deaf children can differ dramatically from the norm, both in modality (as in signed languages) and in quality (as for deaf children exposed exclusively to aural oral language). Such factors affect the development of the cognitive architecture and WM functioning in both verbal and visuo-spatial domains. This chapter reviews evidence pertaining to WM in deaf children and explores potential implications arising from the unique characteristics of the deaf experience.